Molecular markers from coffee genome expressed sequences potentially involved in resistance to rust - Alvarenga, Samuel Mazzinghy; Caixeta, Eveline Teixeira; Hufnagel, Bárbara; Thiebaut, Flávia; Maciel-Zambolim, Eunize; Zambolim, Laércio; Sakiyama, Ney Sussumu (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to identify molecular markers related to the resistance of coffee (Coffea arabica) to rust (Hemileia vastatrix). DNA sequences potentially involved in coffee disease resistance were identified, using “in silico” analysis, from data obtained by the Brazilian coffee genome project. After data mining, 59 primer pairs were designed to amplify the sequences identified. The 59 primers were tested on 12 resistant and 12 susceptible coffee plants to H. vastatrix. Twenty-seven primers resulted in unique and well‑defined bands, while one of these amplified a DNA fragment in all resistant plants, but not in the susceptible ones. This polymorphic molecular marker amplified a region of DNA that corresponds to a partial open reading frame of C. arabica genome that encodes a disease resistance protein. The marker CARF 005 can be used to differentiate between resistant and susceptible coffee plants to H. vastatrix.